Clinical investigation of post blepharoplasty adjuvant carbon dioxide laser resurfacing - Alsagban, Ali Arkan; Alshami, Muhanad Lebnan; Al-Maliky, Mohammed A. (Journal of Pakistan Association of Dermatologists, 2020)
Background Aging is continuous process that affects negatively people social activities. Aesthetic procedures can bring confidence, happiness and improves social relationships. The goal of this study is the evaluation the eyelid skin tightening after the post blepharoplasty adjuvant CO2 laser carried out at one month after the surgery. Methods Eleven patients with age range of 34 to 57 years were treated by blepharoplasty surgery followed by laser resurfacing after one month of the surgery. The first session of laser irradiation were carried out under topical anesthesia at one month from the day of surgery. The degree of wrinkles of both upper and lower eyelids was measured by Image J V 1.51K computer software for the recorded photographs both before and at one month after treatment. Results Descriptive results of the treatment before and after CO2 laser irradiation were 125.53 (±2.17) and 115.13 (±14.55) pixels, respectively. The Wilcoxon Signed Ranks statistical test showed a significant difference between the before and after treatment wrinkles reduction, p=0.016. Conclusion Adding the CO2 laser as assisted tool for this procedure has led to synergistic effect for eyelid skin tightening by 8.3%.